2004
DOI: 10.1128/aac.48.11.4286-4292.2004
|View full text |Cite
|
Sign up to set email alerts
|

Activity of the New Triazole Derivative Albaconazole against Trypanosoma ( Schizotrypanum ) cruzi in Dog Hosts

Abstract: Albaconazole is an experimental triazole derivative with potent and broad-spectrum antifungal activity and a remarkably long half-life in dogs, monkeys, and humans. In the present work, we investigated the in vivo activity of this compound against two strains of the protozoan parasite Trypanosoma (Schizotrypanum) cruzi, the causative agent of Chagas' disease, using dogs as hosts. The T. cruzi strains used in the study were previously characterized (murine model) as susceptible (strain Berenice-78) and partiall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
39
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 74 publications
(45 citation statements)
references
References 31 publications
4
39
0
2
Order By: Relevance
“…However, high IgG1 levels are not always beneficial to the host, since IgG1 can block the activities of different isotypes of anti-T. cruzi antibodies through cross-linking with irrelevant antigens in the defense against the parasite, thus deflecting humoral immunity toward a nonspecific and ineffective response (37,43). According to previous investigations (26,44), the attenuation of the humoral response observed in this study is consistent with the best parasitological control and reduction of the parasite load induced by the cruzi and treated with benznidazole and curcumin. The treated animals received benznidazole (100 or 50 mg/kg) and curcumin (100 mg/kg).…”
Section: Discussionmentioning
confidence: 99%
“…However, high IgG1 levels are not always beneficial to the host, since IgG1 can block the activities of different isotypes of anti-T. cruzi antibodies through cross-linking with irrelevant antigens in the defense against the parasite, thus deflecting humoral immunity toward a nonspecific and ineffective response (37,43). According to previous investigations (26,44), the attenuation of the humoral response observed in this study is consistent with the best parasitological control and reduction of the parasite load induced by the cruzi and treated with benznidazole and curcumin. The treated animals received benznidazole (100 or 50 mg/kg) and curcumin (100 mg/kg).…”
Section: Discussionmentioning
confidence: 99%
“…UR-9825 is another potent fungal and protozoan CYP51 inhibitor with remarkable in vitro anti-T. cruzi activity (Urbina et al 2000). However, its very short half-life in the mouse (< 0.5 h) precluded in vivo studies in this animal model, but work in a canine model has demonstrated that the compound exhibits curative activity against established infections of the virulent Y strain of T. cruzi with very low toxicity, although drug resistance was encountered with the Berenice-78 strain (Guedes et al 2004). Finally, ravuconazole has also been shown to be very active against T. cruzi in vitro, but its in vivo activity in mice was limited, most likely due to inadequate pharmacokinetic properties in this animal model (terminal half-life of 4.5 h) (Urbina et al 2003b).…”
Section: Ergosterol Biosynthesis Inhibitors (Ebi) As Potential New Thmentioning
confidence: 99%
“…1), such as TAK-187 (Takeda Chemical Company) (Urbina et al 2003c, Corrales et al 2005, UR-9825 (Uriach & Company) (Urbina et al 2000, Guedes et al 2004) and ravuconazole (ER-30346, Eisai Co.; BMS 207,147; Bristol-Myers Squibb) (Urbina et al 2003b) also exhibit trypanocidal activity in vitro and in vivo. TAK-187 is a long-lasting triazole derivative with broad-spectrum antifungal activity, which also possesses very potent anti-T. cruzi activity in vitro and is capable of curing both acute and chronic infections in murine hosts even when the infecting strain is resistant to nitrofuran and nitroimidazole (Urbina et al 2003c).…”
Section: Ergosterol Biosynthesis Inhibitors (Ebi) As Potential New Thmentioning
confidence: 99%
“…In addition, they possess pharmacokinetic properties particularly suited to the control of this disseminated intracellular infection. Several triazole derivatives have been experimentally tested, including D0870 (20), posaconazole (POS) (19,43), ravuconazole (44), albaconazole (15), and TAK-187 (42). In particular, POS (Schering-Plough Research Institute) was recently registered for the prophylaxis and treatment of invasive fungal infections in the European Union, Australia, and the United States.…”
mentioning
confidence: 99%